Has the Economic Lockdown Following the Covid-19 Pandemic Changed the Gender Division of Labor in Israel?. Issue 2 (April 2021) - Yaish, Meir; Mandel, Hadas; Kristal, Tali
The economic shutdown and national lockdown following the outbreak of COVID-19 have increased demand for unpaid work at home, particularly among families with children, and reduced demand for paid work. Concurrently, the share of the workforce that has relocated its workplace to home has also increased. In this article, we examine the consequences of these processes for the allocation of time among paid work, housework, and care work for men and women in Israel. Using data on 2, 027 Israeli adults whom we followed since the first week of March (before the spread of COVID-19), we focus on the effect of the second lockdown in Israel (in September) on the gender division of both paid and unpaid work. We find that as demand for housework caused by the lockdown increases, women—especially with children—increase their housework much more than men do, particularly when they work from home. The consequences of work from home and other flexible work arrangements for gender inequality within the family are discussed.